Enhanced nitrogen cycling and N2O loss in water-saving ground cover rice production systems (GCRPS) - Zhe Chen; Shan Lin; Zhisheng Yao; Xunhua Zheng; Gschwendtner, S.; Schloterd, M.; Meiju Liu; Yanan Zhangb; Butterbach-Bahl, Klaus; Dannenmann, Michael (Elsevier, 2018)
An alternative to conventional cultivation of rice on submerged paddy soil is the ground cover rice production system (GCRPS), in which soil is covered with a plastic film to reduce the use of irrigation water. However, reduced soil water, increased aeration and temperature under GCRPS could promote soil nitrogen (N) mineralizing, nitrifying and denitrifying microbes and thus enhance soil N turnover and environmental losses e.g., through emission of the potent greenhouse gas nitrous oxide (N2O). At two sites with paired GCRPS and conventional paddy fields in Central China, we followed the abundance and activity of N-mineralizers, nitrifiers, denitrifiers and N2-fixing microbes based on qPCR from DNA and RNA directly extracted from soil. With decreasing soil water during the growing season, GCRPS strongly increased N mineralization as illustrated by several fold increased transcript levels of chiA. Furthermore, GCRPS reduced the nifH transcripts (encoding for nitrogenase) by 38% to 70% but increased the qnorB transcripts by 160% and archaeal amoA (AOA) transcripts by one order of magnitude (encoding for nitric oxide reductase and ammonia monooxygenase). This indicated a higher potential for N losses due to decreased biological N2 fixation, increased N leaching and increased N2O emission in GCRPS. The latter was confirmed by increased in situ N2O emissions. In addition, the N2-fixing and denitrifying microbial community composition as measured by a community fingerprinting approach was strongly influenced by GCRPS cultivation. Hence, our study reveals the microbial mechanisms underlying the risks for increased N mineralization, nitrification and N2O emissions and decreased biological N fixation in GCRPS. However, analysis of topsoil N stocks provided evidence that at least under N fertilizer application, GCRPS might overall maintain soil N stocks. This might result from a GCRPS-induced increase in fertilizer N use efficiency, root development and C and N return via residues, which appear to outbalance the observed effects on nitrification, gaseous N losses and biological N fixation, thereby preventing a net loss of total soil N.